Storage of Mortgage Maximum in Indonesia Lawyers Club Episode Events (When Ahok Apologizes) - Syahrul, Abdul (Faculty of Teacher Training and Education of Undaris, 2017)
This research aims at describing and explaining the deviation â€œleechâ€ on maxim courtesy at the event of Indonesia Lawyers Club